Design of power divider with bandpass response and notched band. Issue 8 (1st April 2014) - Xiao, Long; Peng, Hao; Yang, Tao
Abstract : A novel multilayer in‐phase slotline power divider with bandpass response and one tunable notched band is proposed. The presented power divider employs the structure of microstrip‐to‐slotline transition to split the input signals over the frequency range 3.5–10 GHz. A wide upper stopband is obtained by using an interdigital configuration and introducing a defected ground structure. A quarter‐wavelength short‐circuited stub is utilised to obtain the tunable notched band in the passband. The experimental results indicate that the proposed power divider has good phase balance, high isolation between output ports, good return losses at all ports and flat group delay over a wide frequency range.